2021
DOI: 10.3390/nu13113928
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Anemia, and Kidney Function among Guatemalan Sugarcane Workers

Abstract: Rates of anemia among agricultural workers, who are also at risk for kidney injury and chronic kidney disease of unknown cause (CKDu), are unknown. We evaluated body composition through the sum of three skinfolds among 203 male sugarcane cutters and assessed the relationship of variables related to nutrition, anemia (hemoglobin < 13 g/dL), and elevated hemoglobin A1c (HbA1c ≥ 5.7%) with estimated glomerular filtration rate (eGFR) using linear regression. Eleven percent of workers were at the level of essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Laboratory test data could also be an underlying predictor of CA-AKI. Several observational studies have demonstrated that albumin has a protective effect against the development of CA-AKI [ 30–32 ]. However, its impact on CA patients has not been documented in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory test data could also be an underlying predictor of CA-AKI. Several observational studies have demonstrated that albumin has a protective effect against the development of CA-AKI [ 30–32 ]. However, its impact on CA patients has not been documented in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Given that exposure to agrochemicals or heavy metals has been hypothesized to play a role in CKDnT, but that available evidence is inconclusive [4][5][6][7][8][9][10][11][12][13], the environmental study of the identified cluster of municipalities offers a promising way forward for testing environmental hypotheses. Similarly, it is known that poverty is associated to traditional risk factors such as diabetes and hypertension, but it may be associated with other factors that affect people at younger ages, such as nutrition, as some studies have found [65], or to other cardiometabolic exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Five-part differential CBC by CELL-DYN Ruby, Haematology Analyzer (USA) (7) . Kidney function test with (Urea, Cr, and Uric Acid) by ARCHITECT Ci4100 Integrated System Instrument (Clinical Chemistry Analyzer and Immunoassay Analyzer) (8) . Clinical chemistry analyzer and immunoassay analyzer, ARCHITECT Ci4100 integrated system device, CRP (9) .…”
Section: Clinical Examinationmentioning
confidence: 99%